Exploring the role of music therapy in attachment, identity & creativity : a case study - Cuddy, James (2016)
Music therapy has been implemented within healthcare to treat individual’s suffering from various forms of illness today. Music and the creative process are a fundamental component human life, bringing order to inner chaos and understanding to our human experience. However the intricacies of the creative process within clinical music therapy leaves many question unanswered and its tangible effects often remain illusive to those outside of the therapeutic process.